Layout timing of mining roadways considering goaf and roof stability - Yuan, Fang; Tang, Jianxin; Kong, Lingrui; Li, Cheng (Frontiers in Earth Science, 2023)
Reasonable roadway layout timing can effectively reduce the deformation of the surrounding rock of the roadway and relieve the tension of mining and excavation. The mine pressure behavior of gob-side entry at the edge of the goaf and the roof stability along the strike direction in the middle of the goaf were analyzed by field observation and PFC numerical simulation. The results showed that the deformation of surrounding rock is mainly roof-to-floor convergence, and the roof-to-floor convergence is mainly floor heave. The mechanical behavior of rock mass such as elasticity, fracture, and post-peak softening can be simulated by using the model of jointed rock mass generated by rigid block elements in PFC. Taking the length and time of the roof violent activity zone and roof activity reduction zone as the index to determine the basic stability of the goaf, the basic stability distance of the goaf edge is 135 m after coal seam mining, and the basic stability time is 27 d. The basic stable distance in the middle of the goaf is 183.4 m after coal seam mining, and the basic stable time is 37 d.